Symmetry in the Holy Qur'an: Psychological Emotions and Counseling Contexts in Taha and Al-Insan Chapters - Al-Qaisy, Lama Majed; Al-Rawajfeh, Aiman Eid (Journal of Educational and Psychological Sciences, 2021)
The present study aimed to identify symmetry in the Holy Qur’an, concerning the psychological and indicative meanings in two corresponding Surahs (chapters) in the Holy Qur'an. These two chapters are Taha and Al-Insan Chapters. In this study, the deductive approach was used. This approach is based on understanding the texts by realizing the exact meaning and knowing the pronunciation and its indications, and then borrowing psychological and indicative meanings. The results of the study indicate that Both Taha and Al-Insan Chapters corresponded in many different psychological and indicative meanings, such as, social support, anger and sadness, happiness and tranquility, self-confidence, and punishment and reinforcement methods. The researchers recommend conducting more research on Symmetry in the Holy Qur'an in other different aspects.
Keywords: Motivation; Social Support; Behavior Modification; Happiness; Reinforcement